2013
DOI: 10.3748/wjg.v19.i44.8042
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis and follow-up of 135 patients with ischemic colitis over a five-year period

Abstract: The five-year recurrence rate of IC was low. On the other hand, mortality during follow-up was high and was not associated with ischemic colitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 21 publications
0
27
0
1
Order By: Relevance
“…On univariate or multivariate analysis, 10 studies [4,5,17,21,22,24,[29][30][31][32] showed that right sided IC was a risk factor of a poor prognosis. In the study by Sotiriadis et al [22], right colonic involvement was associated with a fivefold higher rate of surgery and twice the mortality compared with other locations.…”
Section: Predictors Of Disease Severitymentioning
confidence: 99%
See 2 more Smart Citations
“…On univariate or multivariate analysis, 10 studies [4,5,17,21,22,24,[29][30][31][32] showed that right sided IC was a risk factor of a poor prognosis. In the study by Sotiriadis et al [22], right colonic involvement was associated with a fivefold higher rate of surgery and twice the mortality compared with other locations.…”
Section: Predictors Of Disease Severitymentioning
confidence: 99%
“…Among these the incidence of poor prognosis was 48.4% (134/277), compared with 12.1% (142/ 1175) of patients without right colonic involvement (P = 0.000) ( Table 4). Ten of the 13 studies [4,5,17,21,22,24,[29][30][31][32] reported that right sided IC was a risk factor for a poor prognosis. Clinical heterogeneity among the studies in Table 5 included lack of uniformity of the definition of the anatomical distribution of disease.…”
Section: Right Sided Ischaemic Colitismentioning
confidence: 99%
See 1 more Smart Citation
“…Cosme et al. 34 reported mortalities due to IC in Spain of 5.9% at first admission and 7.4% 5 years later, and overall mortalities, including deaths from comorbidities, of 8.8% and 31.1%, respectively. These rates were high compared with those observed in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…22 Another report comments on 2 patients who died of recurrent colon ischemia after arterial stenting for chronic mesenteric ischemia, but clinical, angiographic, and other details are lacking. 23 Some authors now suggest angiography may be useful when acute mesenteric ischemia is also considered in association with colon ischemia or in some cases of RSCI. 24,25 To our knowledge, this is the first detailed report on symptomatic large visceral artery occlusion and its treatment in survivors of RSCI.…”
Section: Original Research and Contributionsmentioning
confidence: 99%